Enzymatic hydrolysis of lignocellulosic biomass from pineapple leaves by using endo-1,4xylanase : Effect of pH, temperature, enzyme loading and reaction time - N. A. S. M., Rosdee; N., Masngut; S. M., Shaarani; S., Jamek; M. S. M., Sueb (Institute of Physics Publishing, 2020)
Pineapple leaves; is one of lignocellulosic materials that composed of about 80% of carbohydrate containing lignin, cellulose and hemicellulose This waste still retains a considerable amount of soluble sugars that can be transformed into valuable fermentable sugars. This research was conducted to study the effect of different pH, temperature, enzyme loading and reaction time in order to identify the best working conditions to produce the highest yield of sugar. Prior to enzymatic hydrolysis, the pineapple leaves were subjected to hydrothermal pretreatment in order to obtain the hydrolysate liquid. Enzymatic hydrolysis was then carried out by using endo-1,4-xylanase and the reducing sugar was analyzed by using dinitrosalicylic (DNS) method. The result has shown that the highest reducing sugar concentration of 70.9 mg/L was obtained both at pH 5.5 and 50 °C. In addition, the best enzyme loading and reaction time were recorded at 0.5% (w/v) and 45 min that resulted 60.1 mg/L and 72. 0 mg/L respectively.